The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1159/000138616
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Pharmacologic Profile of the Novel Beta-Adrenoceptor Antagonist and Vasodilator, Carvedilol

Abstract: The pharmacologic profile of the novel β-adrenoceptor antagonist/vasodilator, carvedilol, has been investigated in vitro. Carvedilol produced competitive antagonism of the β1-adrenoceptor mediated positive chronotropic response to isoproterenol in guinea pig atria, and the β2-adrenoceptor mediated relaxation to isoproterenol in carbachol (1 μmol/l) precontracted guinea pig trachea, with a dissociation constant (KB) for β1-adrenoceptors of 0.8 nmol/l and β2-adrenocept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…The major findings of the present study are: (1) 3,7,8) and antagonized Bay Kinduced contractions and hypertensive effects. and the inhibitory effect was observed at concentrations higher than 0.2 µM.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The major findings of the present study are: (1) 3,7,8) and antagonized Bay Kinduced contractions and hypertensive effects. and the inhibitory effect was observed at concentrations higher than 0.2 µM.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, carvedilol reduces the contraction induced by membrane depolarization in a high K + medium in isolated rabbit coronary artery and rat aortic preparations. 3,7,8) It also antagonizes the Bay K-induced contraction in vascular smooth muscle. 8) These observations suggest that carvedilol may inhibit voltage-dependent L-type Ca 2+ channels (I Ca.L ) in vascular smooth muscle cells (VSMCs).…”
Section: Inhibitory Effects Of Carvedilol On Calcium Channels In Vascmentioning
confidence: 94%
“…It is β1, β2 antagonist(onset in 1 hour), α1 antagonist( onset in 30 minutes) and on oral administration it is rapidly absorbed and reaches peak plasma concentration within one to 2 hours. At higher doses, it has calcium channel blocking property of moderate potency (blocks L-type voltage gated channels) [11,12] but the effect of this blockade on blood glucose levels is a scantily explored domain [13,14]. Some studies reported beta blocking induced hyperglycaemia contradicting the ideas of its vasodilating property inducing hypoglycaemia by improving insulin sensitivity [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the α-blocking activity of carvedilol in dogs is 3.8 times less potent than the β-blocking activity [19]. In the isolated rabbit aorta, carvedilol is approximately ten-fold less potent as an α 1 -antagonist than as a β-antagonist [29]. In this study, the response of the heart rate to isoproterenol was diminished by 40% with 0.4 mg/kg carvedilol.…”
Section: Discussionmentioning
confidence: 49%
“…Carvedilol's β 2 -adrenergic antagonism also inhibits the β 2 -receptor-mediated relaxation induced by isoproterenol in guinea pig trachea in a concentration-dependent manner [29]. An in vivo study in rats has shown that intravenous carvedilol significantly inhibits the β 2 -adrenoceptor-mediated vasodilator response to salbutamol and suggests that carvedilol inhibits β 1 -and β 2 -adrenoceptors to a similar degree in vivo [30].…”
Section: Discussionmentioning
confidence: 99%